Rapid Production of Cell‐Laden Microspheres Using a Flexible Microfluidic Encapsulation Platform. Issue 47 (30th August 2019) - Seeto, Wen J.; Tian, Yuan; Pradhan, Shantanu; Kerscher, Petra; Lipke, Elizabeth A.
Abstract: This study establishes a novel microfluidic platform for rapid encapsulation of cells at high densities in photocrosslinkable microspherical hydrogels including poly(ethylene glycol)‐diacrylate, poly(ethylene glycol)‐fibrinogen, and gelatin methacrylate. Cell‐laden hydrogel microspheres are advantageous for many applications from drug screening to regenerative medicine. Employing microfluidic systems is considered the most efficient method for scale‐up production of uniform microspheres. However, existing platforms have been constrained by traditional microfabrication techniques for device fabrication, restricting microsphere diameter to below 200 µm and making iterative design changes time‐consuming and costly. Using a new molding technique, the microfluidic device employs a modified T‐junction design with readily adjustable channel sizes, enabling production of highly uniform microspheres with cell densities (10–60 million cells mL −1 ) and a wide range of diameters (300–1100 µm), which are critical for realizing downstream applications, through rapid photocrosslinking (≈1 s per microsphere). Multiple cell types are encapsulated at rates of up to 1 million cells per min, are evenly distributed throughout the microspheres, and maintain high viability and appropriate cellular activities in long‐term culture. This microfluidic encapsulation platform is a valuable and readily adoptable tool for numerous applications, including supporting injectable cell therapy, bioreactor‐based cell expansion and differentiation, and high throughput tissue sphere‐based drug testing assays. Abstract : A novel microfluidic encapsulation platform is designed and used for rapid production of highly uniform cell‐laden hydrogel microspheres with high cell densities and a wide range of sizes, which cannot be achieved using traditional microfluidic chips. With all the features, the resulting microspheres advance the ability to use tissue microspheres for downstream applications including regenerative medicine.